Water level fluctuation controls carbon emission fluxes in a shallow lake in China - Yuan, Xiaomin; Liu, Qiang; Li, Shuzhen; Cui, Baoshan; Yang, Wei; Sun, Tao; Wang, Xuan; Li, Chunhui; Cai, Yanpeng; Li, Miao; Zhou, Jialiang (Frontiers in Earth Science, 2023)
High-strength alterations in the water level due to extreme climate change and increased anthropogenic activities have implications for methane (CH4) and carbon dioxide (CO2) emission variations in shallow lakes. However, the consistency of the carbon emission flux in response to water-level fluctuations and temperature is still unclear. Here, we evaluated the water depth (WD) on the magnitude and variation sensitivity of CH4, CO2, and GHG, and then the temperature dependence of carbon emissions was estimated at different water levels. The water depth threshold indicated a maximum CH4 (97.5 cm) and CO2 (10 cm), resulting in a water depth threshold of GHG at 54.6 cm. Inside the whole WD, the effect of rising water depth on CH4, CO2 and GHG sensitivity shifted from a positive effect to a negative effect at a WD of 97.5 cm. And CH4, CO2 and GHG in 10 cm